Three-dimensional electrospun nanofibrous scaffolds to fabricate in vitro model for liver diseases - Das, Prativa (Nanyang Technological University, 2020)
Liver extracellular matrix, which has random fibrous network structure, can be closely mimicked by the electrospun fibrous scaffolds. Thus, electrospinning is a promising technology to develop scaffolds for liver tissue engineering. However, the closely packed fibrous mat obtained by the conventional electrospinning process restricts cellular infiltration, thus act like a two-dimensional cell culture model which is different from the in vivo three-dimensional microenvironment. In this study, an interdisciplinary approach was applied to construct a three-dimensional liver tissue mimicking scaffold by using the knowledge of material science and molecular biology. A newly optimized wet electrospinning process was applied to prepare three-dimensional scaffolds with random fibrous network structure. The three-dimensional random electrospun fibers mimic the physical microenvironment, whereas the extracellular matrix proteins grafted on the fiber surface by chemisorption process mimics the chemical microenvironment for the human liver cells. Collagen-I and fibronectin, which are two essential liver extracellular matrix proteins were used to modify the fiber surface. The initial findings suggested that collagen-I modified 3D wet electrospun scaffolds were superior compared to both fibronectin modified scaffold and gold standard sandwich culture in maintaining functions of primary human hepatocytes in vitro. Thus, collagen-I modified 3D electrospun scaffold was used for co-culture of primary human hepatocytes with human hepatic stellate cells to establish the optimum ratio of these two liver cells in the in vitro culture. The ratio was optimized by studying the long-term functional maintenance of primary human hepatocytes. The distinct role of collagen-I and fibronectin for in vitro maintenance of primary human hepatocytes were analyzed and these findings leads to further exploration of the combined effect of these two-essential ECM proteins for the culture of human liver cells in vitro. A series of different ratios of collagen-I to fibronectin were used to chemisorb the electrospun scaffolds. The protein amounts were optimized based on total protein absorbed and the homogeneous distribution of both the proteins on the scaffold surface. Improved protein distribution on the fiber surface was found to enhance functional maintenance of human hepatocytes on 3D electrospun fibrous scaffolds. The findings suggested that cellular microenvironment controls translational and transcriptional properties of the liver cells. The optimized 3D electrospun fibrous scaffolds with optimum ratio of human primary hepatocytes and human hepatic stellate cells were used to fabricate an alcoholic liver disease model. The proposed model was analyzed at different dosage of alcohol under different scaffold conditions. The effect of alcohol was found to be more prominent on the cells cultured on the electrospun fibrous scaffolds modified with both collagen-I and fibronectin when compared to the single protein modified scaffolds, unmodified scaffolds and the gold standard sandwich culture. This ECM modified electrospun fibrous scaffolds with human liver cells can be used as an engineered liver tissue for studying the effect of different toxins, fibrosis causing elements or dose dependent study of antifibrotic drugs.